Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Nasal Microbiome in COVID-19: A Potential Role of Corynebacterium in Anosmia - Carmela Nardelli; Giovanni Luca Scaglione; Domenico Testa; Mario Setaro; Filippo Russo; Carmela Di Domenico; Lidia Atripaldi; Massimo Zollo; Federica Corrado; Paola Salvatore; Biagio Pinchera; Ivan Gentile; et al. (Current Microbiology, 2023)
The evolution and the development of the symptoms of Coronavirus disease 19 (COVID-19) are due to different factors, where the microbiome plays a relevant role. The possible relationships between the gut, lung, nasopharyngeal, and oral microbiome with COVID-19 have been investigated. We analyzed the nasal microbiome of both positive and negative SARS-CoV-2 individuals, showing differences in terms of bacterial composition in this niche of respiratory tract. The microbiota solution A (Arrow Diagnostics) was used to cover the hypervariable V1–V3 regions of the bacterial 16S rRNA gene. MicrobAT Suite and MicrobiomeAnalyst program were used to identify the operational taxonomic units (OTUs) and to perform the statistical analysis, respectively. The main taxa identified in nasal microbiome of COVID-19 patients and in Healthy Control subjects belonged to three distinct phyla: Proteobacteria (HC = 14%, Cov19 = 35.8%), Firmicutes (HC = 28.8%, Cov19 = 30.6%), and Actinobacteria (HC = 56.7%, Cov19 = 14.4%) with a relative abundance > 1% in all groups. A significant reduction of Actinobacteria in Cov19 group compared to controls ( P < 0.001, FDR = 0.01) was found. The significant reduction of Actinobacteria was identified in all taxonomic levels down to the genus ( P < 0.01) using the ANOVA test. Indeed, a significantly reduced relative abundance of Corynebacterium was found in the patients compared to healthy controls ( P = 0.001). Reduced abundance of Corynebacterium has been widely associated with anosmia, a common symptom of COVID-19 as suffered from our patients. Contrastingly, the Corynebacterium genus was highly represented in the nasal mucosa of healthy subjects. Further investigations on larger cohorts are necessary to establish functional relationships between nasal microbiota content and clinical features of COVID-19.